Maqashid Sharia Study on Minerals and Coal Law in Indonesia - Ahmad Lutfi Rijalul Fikri (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2024)
Maqashid Sharia is a law-making principle that aims to bring Islamic teachings in line with various contexts encountered, including in today's modern context. This includes the application of Law Number 3 of 2020 concerning Minerals and Coal which has recently become a polemic among the people. Maqashid Sharia analysis is deemed necessary because it is in direct contact with the benefits and harms that will arise from the implementation of this legislation. This research is a normative legal research using a conceptual approach (Maqashid Syariah) and statutory approach (statute approach) with qualitative descriptive and interpretation techniques to find compatibility between the applicable laws and regulations and Maqashid Syaria. The result of this research is that the principles of Maqashid Syaria are accommodated in the Mineral and Coal Law that applies in Indonesia. Where the goal of community welfare or in the language of Islamic law is called Mashlahah 'Ammah contained in this Minerba Law indicates that this law is in accordance with the Shari'a goals in the formation and determination of a law. However, this Minerba Law cannot be separated from criticism regarding the potential for harm arising from the stipulation of several articles which are considered controversial by several legal experts. Therefore, the principle of producing good and avoiding or minimizing bad is a basic principle in Maqshid Syariah that legislators should pay attention to in making a law so that the resulting statutory decisions are in line with shari’a goals.